BUREAUCRATIC REFORM IN JAKARTA: JOKOWI LEADERSHIP STYLE - Jerry Indrawan (The Indonesian Journal of Public Administration (IJPA), 2016)
ABSTRACT Jakarta is still facing many problems regarding bureaucratic system. It positions as the state capital does not guarantee that bureaucratic reform has already establish in perfect manner. At least there are three problems that need to be reformed. First, corruption in three fields: administrative services, practices of construction projects, and law enforcement. Second, institutional inefficiency. The local government bureaucratic structure is too fat, because of too many departments and sections exist, and resulting in the amount of local budget use to cover it. Third, corruptive mentality from most of the civil servants, resulting in deficient public services. Joko Widodo, better known as Jokowi is a new Governor of Jakarta. Before, he was a Mayor in Solo, Central Java for seven years. He brought bureaucratic reform to that city, that leads him in winning various national, even international achievements, such as the World Third Best Mayor from The City Mayor Foundation. Jokowi success is mostly because of his leadership ability. His leadership style is also different than others. There is no gap between him and his people. There is no strict protocol either that restrain him in meeting his people anytime he likes. He ignored bureaucratic formality, because such will dissociate him with his people. One of his well known method is “blusukan”, which means “entering a place where nobody wants to” in Javanese. He applied “blusukan” as a way in knowing what people wants by visiting them, even to a slum area where no public officials even care to think. In doing this, he can see the real problem in the society and starts to reform the government based in his field observation. He minimized the long arm of bureaucracy, in terms of efficiency and knowing what’s best for his people. He even said that he will only spend one hour every day in the office, and the rest (include saturday and sunday) will be spent in the field. He thinks that the only way we know the problem lies on this city is experience it, and the experience will not be experienced by staying in the office. He has to be with his people, so that he can find a solution for them. This paper will see Jokowi leadership style in leading Jakarta and the influence it makes to reform Jakarta’s local government bureaucratic system. Does Jokowi leadership style will be the perfect answer to the city real problems nowadays? Conducted research methodology was qualitative, through library research. The primary data will be collected from interviews with related informants. The informants will be purposively determined to sharpen the information gathered. Last, the secondary data will be aquired from books, journals, internet, newspapers, etc.   Keywords: Bureaucratic Reform, Leadership Style, “Blusukan”